Improving Listening Skills Through Storytelling Methods with Digital Storybooks in Early Childhood - Sari, Suciyanik Nilam; Kumala, Farida Nur; Muntomimah, Siti (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2025)
This study aims to enhance the listening comprehension skills of 5-6-year-old children at TK Mutiara Hati Ngantang through the storytelling method using digital storybooks. The research method employed is Classroom Action Research (CAR) with the spiral model of Kemmis and McTaggart, consisting of two cycles, each with two meetings. Data were collected through observation, interviews, and documentation, and analyzed using the Miles & Huberman data analysis model, which includes data reduction, data presentation, and conclusion drawing. The results show a significant improvement in the children’s listening comprehension after the implementation of the digital storybook storytelling method. In the initial observation, only 33.3% of children were categorized as emerging. However, in cycle 1, the first meeting showed a 40% improvement, and the second meeting reached 53.3%. Cycle 2 showed even greater progress, with the first meeting achieving 66.6% and the second meeting reaching 86.6%. These results indicate that the use of digital storybooks effectively helps children comprehend the story content, retell the story in the correct sequence, and follow more complex instructions. In conclusion, the storytelling method using digital storybooks is proven to be an effective tool in improving listening comprehension skills in 5-6-year-old children. The significant improvements in listening comprehension, along with the children’s increased enthusiasm and focus, highlight the potential of digital storybooks as an engaging and interactive learning medium for early childhood education.